HOME ENVIRONMENTS OF INFANTS FROM IMMIGRANT FAMILIES IN THE UNITED STATES: FINDINGS FROM THE NEW IMMIGRANT SURVEY. Issue 6 (10th October 2014) - Bradley, Robert H.; Pennar, Amy; Glick, Jennifer
ABSTRACT Data from the New Immigrant Survey were used to describe the home environments of 638 children ages birth to 3 years whose parents legally immigrated to the United States. Thirty‐two indicators of home conditions were clustered into four domains: discipline and socioemotional in support, learning materials, enriching experiences, and family activities. Results revealed variation in how frequently infants from every country (Mexico, El Salvador, India, Philippines) and region (East Asia, Europe, Caribbean, Africa) studied experienced each home environmental condition. There were differences between countries and regions on many indicators as well as differences based on parents' level of education. The experiences documented for children of recent legal immigrants were similar to those documented for children of native‐born families in other studies.